2021
DOI: 10.1002/term.3237
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of gellan gum hydrogel reinforced with silk fibers with enhanced mechanical and biological properties for cartilage tissue engineering

Abstract: Various research about cartilage regeneration using biomaterials has been done recently. Particularly, gellan gum hydrogel (GG) is reported to be suitable as a biomaterial for cartilage tissue engineering (TE) for its water uptaking ability, producibility, and environmental resemblance of native cartilage. Despite these advantages, mechanical and cell adhesion properties are still difficult to modulate.Reinforcement is essential to overcome these problems. Herein, GG was modified by physically blending with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Various studies have been reported to improve the mechanical properties of soft tissue scaffolds, and they achieve modulus ranging from KPa to MPa [ 52 ]. In a study, silk fibers were used as reinforcement to improve the mechanical properties of gellan gum hydrogel, but could achieve a maximum of 0.4 MPa modulus [ 53 ]. In another study, hydrogel for tissue engineering scaffolds has been developed using sodium alginate, gelatin, and soy protein powder and could get a 256.7 kPa modulus [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have been reported to improve the mechanical properties of soft tissue scaffolds, and they achieve modulus ranging from KPa to MPa [ 52 ]. In a study, silk fibers were used as reinforcement to improve the mechanical properties of gellan gum hydrogel, but could achieve a maximum of 0.4 MPa modulus [ 53 ]. In another study, hydrogel for tissue engineering scaffolds has been developed using sodium alginate, gelatin, and soy protein powder and could get a 256.7 kPa modulus [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reinforcing hydrogels with silk microfibres broadens their use in biomedical and engineering applications. For example, fibre-reinforced hydrogels have increased mechanical strength, making them useful for hard tissue engineering applications [ 14 , 15 , 32 ]. This ability to tune the hydrogel mechanical properties is critical as it enables matching of the construct to a wider set of target tissues (which can have a broad spectrum of mechanics).…”
Section: Discussionmentioning
confidence: 99%
“…GG is viewed as a promising material in tissue engineering and regenerative medicine as a result of this. The extensive use of GG in the engineering of spinal cord injury regeneration and the regeneration of cartilage, bone, osteochondral, and other tissues is evidence of this [211][212][213]. Table 3 shows the use of biomaterials to generate 3D tumor models.…”
Section: Synthetic and Composite Biomaterialsmentioning
confidence: 99%